Uji Performansi Insinerator Sampah Residu Dengan Variasi Kecepatan Udara Pembakaran - Wisprantoko, Fadhil Alfarel; Winaya, I Nyoman Suprapta; Suryawan, I Gede Putu Agus; Darma, I Wayan Arya (Teknik Desain Mekanika; Vol 10 No 4 (2021): Oktober 2021 : Teknik Desain Mekanika, 2021)
Abstractt Bali is one of the most famous tourist destinations in the world with the number of tourist visits in Bali in 2019 reaching 6.2 million tourists. This causes the accumulation of the amount of waste in the landfill such as organic, inorganic, and residual waste that cannot be recycled, increasing day by day. Incinerator is an alternative technology for processing waste that can convert waste into gas and ash by using the combustion method at high temperatures. Air velocity in the combustion process is one of the important indicators in incinerator performance because it determines the quality of combustion in the incinerator reactor Variations in the combustion air velocity used in this study were 2 m/s, 3 m/s, 4 m/s, 5 m/s, and 6 m/s. Based on all indicators of residual waste incinerator performance obtained in this study, it can be concluded that the variation of air velocity 4 m/s is the best variation of air velocity because the exhaust gas content shows a good combustion process, the highest combustion rate (5.413 kg/hour), the lowest rate of use of diesel fuel (0.105 L/hour), the highest thermal capacity (87.057 MJ/hour), and good and fairly high combustion efficiency (95.16031 %). Keywords: Incinerator, Residual Waste, Combustion Air Velocity Variation, Performance